Oxidation and phase transition in covalently functionalized MoS2 - Moses Badlyan, Narine; Pettinger, Nina; Enderlein, Niklas; Gillen, Roland; Chen, Xin; Zhang, Wanzheng; Knirsch, Kathrin; Hirsch, Andreas; Maultzsch, Janina (Physical Review B, 2022)
We present a Raman study of MoS2 powders and MoS2 individual layers covalently functionalized with organic molecules. In MoS2 powders, the defect-induced "LA"Raman mode shows evidence for successful functionalization. Increasing temperature induces oxidation of both functionalized and nonfunctionalized MoS2 into MoO3. In contrast, mechanically exfoliated individual MoS2 layers do not transfer into MoO3 under the same conditions. Instead, the Raman spectra show that the procedure of covalent functionalization leads to a partial transition from the 2H into the 1T' crystallographic phase in few-layer MoS2. We support the identification of the 1T' phase by DFT calculations of the corresponding vibrational modes in the mono- and bilayer 1T'-MoS2.
CRIS-Team Scopus Importer:2022-09-30